Risk factors of malnutrition in children with congenital heart disease: a meta-analysis - Zhang, Chen; Xu, Banghong; Zhu, Cuiying; Pu, Kai; Bian, Lanzheng (Frontiers in Pediatrics, 2024)
Background: The associated factors of malnutrition in children with congenital heart disease (CHD) must be evaluated to provide evidence for the treatment and care of such children. Methods: Two investigators searched the PubMed database until 25 June 2023 for literature about the associated factors of malnutrition in children with CHD. A meta-analysis of associated factors of malnutrition was performed by RevMan 5.3 software. Results: Thirteen studies involving 8031 children with CHD were included. Pulmonary hypertension (OR=3.81, 95% CI: 2.46–4.12), low birth weight (OR=2.69, 95% CI: 1.25–5.77) and parents’ height (OR=2.15, 95% CI: 1.89–2.92) were the associated factors of growth retardation (all P<0.05). Pulmonary hypertension (OR=3.77, 95% CI: 3.13–4.24), low birth weight (OR=3.04, 95% CI: 2.61–4.18) and pneumonia (OR=2.35, 95% CI: 2.08–2.83) were the associated factors of low body weight of children with CHD (all P<0.05). Conclusions: Medical staff should fully understand the risk factors, strengthen nutritional support and enhance nursing care for children with CHD to reduce malnutrition.